Insight into the investigation of diamond nanoparticles suspended therminol 55 nanoﬂuids on concentrated photovoltaic/thermal solar collector - Das, Likhan; Rubbi, Fazlay; Khairul, Habib; Aslfattahi, Navid; Rahman, Saidur; Yahya, Syed Mohd; Kadirgama, Kumaran (MDPI AG, 2022)
Nanofluids are identified as advanced working fluids in the solar energy conversion field with superior heat transfer characteristics. This research work introduces carbon-based diamond nanomaterial and Therminol®55 oil-based nanofluids for implementation in a concentrated photovoltaic/thermal (CPV/T) solar collector. This study focuses on the experimental formulation, characterization of properties, and performance evaluation of the nanofluid-based CPV/T system. Thermo-physical (thermal conductivity, viscosity, and rheology), optical (UV-vis and FT-IR), and stability (Zeta potential) properties of the formulated nanofluids are characterized at 0.001–0.1 wt.% concentrations of dispersed particles using experimental assessment. The maximum photo-thermal energy conversion efficiency of the base fluid is improved by 120.80% at 0.1 wt.%. The thermal conductivity of pure oil is increased by adding the nanomaterial. The highest enhancement of 73.39% is observed for the TH-55/DP nanofluid. Furthermore, dynamic viscosity decreased dramatically across the temperature range studied (20–100 °C), and the nanofluid exhibited dominant Newtonian flow behavior, with viscosity remaining nearly constant up to a shear rate of 100 s−1. Numerical simulations of the nanofluid-operated CPV/T collector have disclosed substantial improvements. At a concentrated solar irradiance of 5000 W/m2 and an optimal flow rate of 3 L/min, the highest thermal and electrical energy conversion efficiency enhancements are found to be 11 and 1.8%, respectively.